Nearly 1.1 million people in Germany use food banks, single and separated parents in particular at an above-average frequency - Markus M. Grabka; Jürgen Schupp (DIW Weekly Report, 2022)
Food banks are returning to the spotlight as their use increases due to the coronavirus pandemic and the influx of Ukrainian refugees to Germany. The current discussion is focused on whether the food banks can handle the increasing number of users as well as the financial and organizational challenges that come with them. Until now, however, no robust, empirical data on food bank use has been available. Using Socio-Economic Panel (SOEP) data, this Weekly Report presents new findings and analyses on the number of food bank users and their socio-demographic distribution. According to the SOEP data, about 1.1 million people used food banks in the first half of 2020. A large share of users are women, people with a migration background, divorced or separated people, and the unemployed; additionally, one fourth of those who benefit from food banks are children. Food bank users also tend to be in poor health. As expected, they also have a below average net household income and accordingly, over two thirds of them are at risk of poverty. The structural causes of poverty must be addressed to ensure that food banks do not reach their limit. Increasing the standard rate for welfare benefits and providing targeted support measures for job seekers could lessen dependency on food banks. Food banks should also be professionalized, as is currently under discussion, and increasingly take on a pilot function for other support measures in the social security system.
Keywords: D31; I31; J31; 330; food banks; SOEP; poverty